Apolipoprotein E4 is associated with improved cognitive function in Amazonian forager‐horticulturalists with a high parasite burden. Issue 4 (28th December 2016) - Trumble, Benjamin C.; Stieglitz, Jonathan; Blackwell, Aaron D.; Allayee, Hooman; Beheim, Bret; Finch, Caleb E.; Gurven, Michael; Kaplan, Hillard
Abstract : The apolipoprotein E4 (E4) allele is present worldwide, despite its associations with higher risk of cardiovascular morbidity, accelerated cognitive decline during aging, and Alzheimer's disease (AD). The E4 allele is especially prevalent in some tropical regions with a high parasite burden. Equatorial populations also face a potential dual burden of high E4 prevalence combined with parasitic infections that can also reduce cognitive performance. We examined the interactions of E4, parasite burden, and cognitive performance in a traditional, nonindustrialized population of Amazonian forager‐horticulturalists ( N = 372) to test whether E4 protects against cognitive decline in environments with a heavy pathogen burden. Contrary to observations in industrial pop‐ulations, older adult E4 carriers with high parasite burdens either maintained or showed slight improvements in cognitive performance, whereas non‐E4 carriers with a high parasite burden showed reduced cognitive performance. Being an E4 carrier is the strongest risk factor to date of AD and cognitive decline in industrial populations; it is associated with greater cognitive performance in individuals facing a high parasite and pathogen load, suggesting advantages to the E4 allele under certain environmental conditions. The current mismatch between postindustrial hygienic lifestyles and active parasite‐rich environs may be critical for understanding genetic risk for cognitive aging. —Trumble, B. C., Stieglitz, J., Blackwell, A. D., Allayee, H., Beheim, B., Finch, C. E., Gurven, M., Kaplan, H. Apolipoprotein E4 is associated with improved cognitive function in Amazonian forager‐horticulturalists with a high parasite burden. FASEB J . 31, 1508–1515 (2017) www.fasebj.org